OUTSOURCING IN HEALTHCARE, CHANGES IN SUS MANAGEMENT AND WORK RELATIONS IN A NEOLIBERAL BRAZIL - Iacer Bueno Carneiro, Anderson; Murilo Leite, Caio; Santiago, Rafael (Health and Society, 2024)
Labor relations have been adapting to new legislation and the market profile over the years, a way that broadens a debate in the health sector, correlating changes in the management of the Unified Health System (SUS) and the arrival of the provision of services, by the cooperative entities, with a contractual configuration,which reinforces the labor issue and expresses the scenario of neoliberalism in Brazil. The present research aims to raise the discussions present in the cited parts, having the versions, such as unions, associations and workers’representatives,which present a critical position and point to the precariousness of labor relations, fearing the lack of inspection of resources transferred in the current model, while public managers and service providers say they are able to meet the demands and contracts signed with municipalities and states, so that health outsourcing takes place in our country. Legislation in constant adaptation seeking to guide the quality assistance to the health user seeking a political and social balance. For this, a bibliographic review was carried out on the proposed themes, with the main and most recent articles found. In this way, it is considered that in a country that descends from slavery and exploitation of cheap labor, the problem is not that social spending fits in the public budget, but that universal rights fit in the psyche of the elites, who are indignant with basic rights offered the working class.